Functional Increase of Brain Histaminergic Signaling in Huntington's Disease - van Wamelen, Daniel J. (Brain Pathol, 2010)
To evaluate whether central histaminergic signaling in Huntington's disease (HD) patients is affected, we assessed mRNA levels of histidine decarboxylase (HDC), volume of and neuron number in the hypothalamic tuberomamillary nucleus (TMN) (HD n = 8, controls n = 8). In addition, we assessed histamine N‐methyltransferase (HMT) and histamine receptor (H(1)R, H(2)R and H(3)R) mRNA levels in the inferior frontal gyrus (IFG) (n = 9 and 9) and caudate nucleus (CN) (n = 6 and 6) by real‐time polymerase chain reaction. In HD patients, TMN volume and neuronal number was unaltered (P = 0.72, P = 0.25). The levels of HDC mRNA (P = 0.046), IFG HMT (P < 0.001), H(1)R (P < 0.001) and H(3)R mRNA levels (P = 0.011) were increased, while CN H(2)R and H(3)R mRNA levels were decreased (P = 0.041, P = 0.009). In HD patients, we observed a positive correlation between IFG H(3)R mRNA levels and CAG repeat length (P = 0.024) and negative correlations between age at onset of disease and IFG HMT (P = 0.015) and H(1)R (P = 0.021) mRNA levels. These findings indicate a functional increase in brain histaminergic signaling in HD, and provide a rationale for the use of histamine receptor antagonists.